2019
DOI: 10.3390/su11061778
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Riverine Habitats in Taiwan Have Spatio-Temporal Consequences, Re-Distributing Caprimulgus affinis into Urban Areas Leading to a Human–Wildlife Conflict

Abstract: Caprimulgus affinis is an endemic species commonly known as the Taiwan nighthawk, forest nighthawk, or South Asian nighthawk. In recent years, the C. affinis population has gradually moved outward from river habitats into the metropolitan areas of Taiwan. Because male birds’ booming sounds at night can reach up to 90 dB or higher and they can be intermittently tweeting for more than 10 hours, they often disturb the sleep of urban residents and can even cause nightmares. In this study, we analyzed long-term sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Previously, this species tends to occupy natural habitats like savannah and river areas around forest. Yet, the rapid development of semi-natural ecosystems in the middle of urban areas has attracted this species to populate urban areas by nesting on tall buildings' roofs (Cheng et al 2019). For example, Iswandaru et al (2020) reported on the existence of Savanna Nightjar around the University of Lampung, Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, this species tends to occupy natural habitats like savannah and river areas around forest. Yet, the rapid development of semi-natural ecosystems in the middle of urban areas has attracted this species to populate urban areas by nesting on tall buildings' roofs (Cheng et al 2019). For example, Iswandaru et al (2020) reported on the existence of Savanna Nightjar around the University of Lampung, Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a variety of methods have been used to analyse species' spatial and/or temporal distributions with citizen science data. These methods include GLMs (Cheng et al, 2019), occupancy models (Altwegg & Nichols, 2019), maximum entropy models (Phillips et al, 2006) and generalized additive models (GAMs) typically using splines as basis functions (Bird et al, 2014). Tree‐based models have also been used, in particular random forests (Prasad et al, 2006) and gradient boosted trees (Elith et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of bird species have been observed to survive successfully in urban environments 36 , 37 . In Taiwan, the savanna nightjar has become one of the most successful urban residents 38 . To better understand their acoustic adaptation to noisy urban environments, we investigated the acoustic structures of individual males’ territorial calls using two proposed hypotheses (see “ Introduction ” for details): no frequency shifting and transmission efficacy of vocal individuality.…”
Section: Discussionmentioning
confidence: 99%